El rol del Estado y su influencia en las condiciones de vida de la mujer desplazada. Medellín, 2015 (2017)
This article intends to present the understanding that women in displacement have made about the role played by the State and its influence on the living conditions of displaced women. It starts from a qualitative approach, taking for the analysis elements of the reasoned theory of Strauss and Corbin. The sample consisted of 49 women in displacement situation. For the analysis we used coding, categorization and interpretation and finally theorization was carried out. The role of the Colombian State influences from the experience of displacement to the perception of health/illness and the search for solutions in health, since it has provided multiple laws for the protection of displaced women, but they have rarely been fulfilled.